Sharing the wealth: The versatility of proteins targeted to peroxisomes and other organelles - Bittner, Elena; Stehlik, Thorsten; Freitag, Johannes (Frontiers in Cell and Developmental Biology, 2022)
Peroxisomes are near ubiquitous eukaryotic organelles with critical functions in cellular energy and lipid metabolism. Depending on the organism, cell type and developmental stage, they are involved in numerous other metabolic and regulatory pathways. Many peroxisomal functions require factors also relevant to other cellular compartments. Here, we review proteins shared by peroxisomes and at least one different site within the cell. We discuss the mechanisms to achieve dual targeting, their regulation and functional consequences. Characterization of dual targeting is fundamental to understand how peroxisomes are integrated in the metabolic and regulatory circuits of eukaryotic cells.